PEMBERDAYAAN PETANI MELALUI INOVASI TEKNOLOGI PASCAPANEN JAGUNG DAN DIVERSIFIKASI PRODUK PANGAN LOKAL BERGIZI UNTUK PENGUATAN KETAHANAN EKONOMI DESA KUALA DUA - Tri Wahyudi; Andang Firmansyah; Shenny Oktoriana; Ratih Rahmahwati; Jurista Purnama Jumri; Agustiah Wulandari (Universitas Mataram, 2026)
Kubu Raya Regency is the second-largest corn (Zea mays L) producer of corn after Bengkayang Regency in West Kalimantan. Kubu Raya Regency has launched a food security and food barn program through the cultivation of corn kernels on a minimum of 1 hectare of corn kernels in each village. However, corn kernel production in Kubu Raya has not yet met the target. The average corn production in Kubu Raya is only around 29 quintals/hectare, while Bengkayang Regency can reach 39 quintals/hectare. This indicates indications of problems in agribusiness development such as the lack of implementation of Appropriate Technology (TTG). The purpose of this empowerment activity is through technological transformation and innovation provided by introducing and implementing science and technology in the form of Appropriate Technology (TTG) resulting from research and patents of the Implementation Team. This empowerment activity also supports the Food Security program of Kubu Raya Regency. The partner in this activity is the Rajawali Farmers Group which is engaged in plantations and horticultural crops. The main focus of the Rajawali Farmers Group is corn cultivation. The second partner in this activity is the Women's Farmers Group (KWT)